Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s11606-020-06407-8
|View full text |Cite
|
Sign up to set email alerts
|

What is the Prevalence of Low Health Literacy in European Union Member States? A Systematic Review and Meta-analysis

Abstract: Background Many studies have shown that low health literacy (HL) is associated with several adverse outcomes. In this study, we systematically reviewed the prevalence of low HL in Europe. Methods PubMed, Embase, and Scopus were searched. Cross-sectional studies conducted in the European Union (EU), published from 2000, investigating the prevalence of low HL in adults using a reliable tool, were included. Quality was assessed with the Newcastle-Ottawa Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 87 publications
2
62
0
Order By: Relevance
“…Self-management strategies, such as taking medications, for successful prevention and management of chronic diseases often require skills to look for and understand essential health information and interact with healthcare professionals [ 2 ]. Low HL levels in this regard is a common challenge shared by many patients globally [ 3 ]. In Europe, on average, 1 in 2 individuals cannot understand essential health information, while slightly lower rates of inadequate HL have been noted in the countries to the north, including Denmark, with around 1 in 5 individuals lacking the ability to understand essential health information [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-management strategies, such as taking medications, for successful prevention and management of chronic diseases often require skills to look for and understand essential health information and interact with healthcare professionals [ 2 ]. Low HL levels in this regard is a common challenge shared by many patients globally [ 3 ]. In Europe, on average, 1 in 2 individuals cannot understand essential health information, while slightly lower rates of inadequate HL have been noted in the countries to the north, including Denmark, with around 1 in 5 individuals lacking the ability to understand essential health information [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low HL levels in this regard is a common challenge shared by many patients globally [ 3 ]. In Europe, on average, 1 in 2 individuals cannot understand essential health information, while slightly lower rates of inadequate HL have been noted in the countries to the north, including Denmark, with around 1 in 5 individuals lacking the ability to understand essential health information [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in different parts of the world have shown that low or limited health literacy in the US, Southeast Asia, and the European Union are prevalent and consistently associated with several factors such as education, ethnicity, and age. In Europe, one in every two Europeans may not be able to comprehend essential health-related information and materials [72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…A abundant of studies indicated that health literacy level vary greatly in epidemiological investigation among different countries and population, and compared with developed countries from Europe and America, Asian population have a higher proportion of low health literacy. For example, Recent metaanalysis including European Union Member States showed that low health literacy account for 27-48% among European [2]. Similarly, nding from American population-based meta-analysis reported that the prevalence of low health literacy was 26% [3].…”
Section: Introductionmentioning
confidence: 99%